(untitled) (UNED Research Journal, 2014)
Productive response of rabbits fed with fresh leaves of nacedero (Trichanthera gigantea, Lamiales:Acanthaceae). Rabbit production is a viable activity in Costa Rica. It offers consumers a high quality meat, and for farmers a good income with a relatively low investment. Production performance, including weight gain and dressing percentage of rabbits fed with two levels of fresh “nacedero” leaves (Trichanthera gigantea) were evaluated. The experiment was conducted in a commercial farm, using 30 weanling animals (California breed) randomly distributed among three treatments (ten animals per treatment): T1: Control: 100% commercial extruded diet, T2: 85:15, 85% commercial extruded diet and 15% nacedero fresh leaves, T3: 70:30, 70% commercial extruded diet and 30% nacedero fresh leaves. Animals were individually weighed weekly for eight weeks, then slaughtered at 88 days of age and dressing percentage calculated. Significant differences (p<0,05) were found between animals from treatments 1 and 2 compared to treatment 3 according to Tukey test. Treatment 3 showed the lowest final weight (p=0,003), weight gain (p=0,008) and dressing percentage (p=0,002). Animals´ initial weights (included as a covariable) had an important effect in all parameter responses (p=0,02). Average initial weights were 441, 403 and 418 g; weight gain was 19, 19 and 17 g/animal/day and dressing percentage was 55, 54 and 51% for animals from treatments 1, 2 and 3 respectively. Dry matter intake was significantly less in animals from treatments 2 and 3 compared to control (p<0,05). It is suggested that 15% of substitution of fresh nacedero foliage in diets for fattening rabbits did not affect productive performance; and improve the use of plants with high potential as forages in productive systems with small animal` species.